THE EFFECT OF TOTAL ASSETS, OWN CAPITAL, MEMBER LOAN AND OPERATIONAL COSTS ON THE REMAINING OF BUSINESS RESULTS IN COOPERATIVES (CASE STUDY ON KP-RI TUNAS BAKTI SMPN 01 KAMPAR AIRTIRIS) - Muhammad Sopian; Arman Arman; Sri Mulyani (STIE Bangkinang Publishing, 2021)
This study was conducted to The Effect of Total Assets, Own Capital, Member Loan and Operational Costs On The Remaining of Business Results In Cooperatives (Case Study On KP-RI Tunas Bakti SMPN 01 Kampar Airtiris). The population in this study was the cooperative KP-RI Tunas Bakti SMPN 01 Kampar Airtiris. The technique used in sampling is the File Research method that comes from the cooperative. Hypothesis testing uses multiple linear regression analysis with the help of SPSS 23.00 for windows. The results showed that simultaneously Total Assets, Own Capital, Member Loans and Operational Costs affect the remaining business results. Partially, namely Total Assets, Own Capital and Member Loans which affect the Remaining Business Results while Operational Costs do not affect the Remaining Business Results.